Influence of Saturant on Seismoelectric Coupling Response of Porous Media - Jufar, S.R. (Institute of Physics Publishing, 2017)
The seismoelectric coupling phenomenon in porous medium saturated with gas and water was studied numerically. The numerical model was formulated based on Pride's theoretically developed seismoelectric coupling coefficient that describes conversion of seismic energy into electromagnetic radiation. The conversion is complex function of physical, electrical and poroelastic properties of the porous medium and the saturant. In this study, a porous medium that is partially saturated with water is considered. Pore spaces that are not saturated with water are considered to be filled with gas. The gas phase is methane. The water saturation was varied from 0.2 to 0.9. The physical and electrical properties of both phases are determined at a temperature of 325 °K. The porosity and permeability of the porous medium is 0.2 and 500 mD, respectively. The porous medium in this study is isotropic. Zeta potential was estimated using an empirically derived correlation. At 0.001 mol/lit salinity, zeta potential is 66.7 mv. The numerical study result shows that at a fixed seismic wave frequency, lower water saturation results in higher seismoelectric coupling coefficient. When water saturation increases, the seismoelectric coupling coefficient decreases. However, the rate of decline is lower at higher seismic frequency. The rate of decline at 10 kHz is 1.38 nV/Pa compared to 4.35 nV/Pa at 100 kHz. Higher frequencies result in stronger nonlinearities, which causes higher mechanical energy dissipation. As such, the result obtained in this study is consistent with what is normally expected when mechanical wave propagates through a porous media. © Published under licence by IOP Publishing Ltd.